2022
DOI: 10.1084/jem.20200418
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 acts as a novel therapeutic target in pathological cardiac hypertrophy and heart failure

Abstract: Circulating proteomic signatures of age are closely associated with aging and age-related diseases; however, the utility of changes in secreted proteins in identifying therapeutic targets for diseases remains unclear. Serum proteomic profiling of an age-stratified healthy population and further community-based cohort together with heart failure patients study demonstrated that circulating C-C motif chemokine ligand 17 (CCL17) level increased with age and correlated with cardiac dysfunction. Subsequent animal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“… 3 Here we demonstrated that CCL17 is a key regulator of vascular aging and CCL17 could serve as a therapeutic target. Previous works from our laboratory and other scientists have demonstrated that CCL17 regulated T cells to promote cardiac aging, 6 , 9 which may be also the potential mechanism underlying vascular aging because we observed such reprogramming of the immune microenvironment (T cells balance) in vascular aging. Further in-depth analysis is still needed to explore CCL17 in reprogramming the immune microenvironment during cardiovascular aging.…”
supporting
confidence: 59%
See 4 more Smart Citations
“… 3 Here we demonstrated that CCL17 is a key regulator of vascular aging and CCL17 could serve as a therapeutic target. Previous works from our laboratory and other scientists have demonstrated that CCL17 regulated T cells to promote cardiac aging, 6 , 9 which may be also the potential mechanism underlying vascular aging because we observed such reprogramming of the immune microenvironment (T cells balance) in vascular aging. Further in-depth analysis is still needed to explore CCL17 in reprogramming the immune microenvironment during cardiovascular aging.…”
supporting
confidence: 59%
“…The serum CCL17 level was increased by Ang II infusion but diminished by CCL17-neutralizing antibodies without any effects on blood pressure or heart rate (Supplementary Tables 2 and 3 ). 6 CCL17 antibody repressed Ang II-induced vascular arterial stiffness and constriction-relaxation dysfunction (Fig. 1h, i ), and reduced aortic remodeling, fibrosis, cell senescence, and senescence-associated secretory phenotype, elastin fiber breakage, coupled with reprogrammed immune microenvironment (Fig.…”
mentioning
confidence: 96%
See 3 more Smart Citations